EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL ON STUDENT LEARNING OUTCOMES IN GEOMETRIC OPTICS SUBMATTER - Rani Deliana Panggabean; Pintor Simamora (Universitas Negeri Medan, 2016)
The study was aimed to determine the effect of Problem Based Learning (PBL) model towards student outcomes and learning activity in optica Geometric material. The type of this research was quasy experiment. The population of this research was all of the students class X SMA Negeri 5 Medan A.Y 2014/2015 which was consist of 5 classes. X MIA 5 was choosen as experimental group and X MIA 3 as Control group by using cluster random sampling. The Instrument used was learning outcomes and student’ activity observation sheet. Based on the hypothesis of the average value, pretest shows that both of the class had the same early abilities. After the treatment, found that the average value of post-test in experimental class by using problem-based learning was 76,34 and control class by using conventional learning was 72,56. The result of test showed that data normally distribution and homegeneous. Then, was made a hypothesis experiment that giving t count (1,83)> t table(1,67), so Ha was accepted. Later, from the observation data showed that the students learning activity in experimental group was belong to the active category. Finally, it could be concluded that there was an effect of Problem based learning model towards the learning outcames and learning activity in optical geometric material.